KAJIAN KUAT TEKAN BETON RINGAN TIDAK TERKEKANG BERAGREGAT KASAR POLIPROPILENA DILAPISI PASIR - Waoma, Adolf; Purnomo, Heru; Musalamah, Sittati (Construction and Material Journal, 2025)
This study aims to determine the compressive strength, density, and crack pattern of lightweight concrete utilizing polypropylene coated with sand as coarse aggregate and Tayan sand as fine aggregate. The research employs three mix design clusters based on the water-to-cement ratio (w/c): Cluster A with a w/c ratio of 0.347, Cluster B with a w/c ratio of 0.339, and Cluster C with a w/c ratio of 0.319. Cylinder-shaped specimens measuring 15×30 cm were prepared for each cluster. For the 15×30 cm cylinder specimens, the average compressive strength obtained was 21.69 MPa, 22.15 MPa, and 24.53 MPa for Clusters A, B, and C, respectively, with standard deviations of 0.59, 0.49, and 1.51. The density of lightweight concrete was recorded as 1717.54 kg/m³, 1689.17 kg/m³, and 1802.93 kg/m³ for Clusters A, B, and C, respectively. The observed crack pattern corresponds to Type 3, in reference to ASTM C39. Keywords: Lightweight Concrete; Polypropylene; Tayan